2014
DOI: 10.1002/em.21864
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach to the in vivo genotoxic effects of a titanium dioxide nanomaterial using LacZ plasmid‐based transgenic mice

Abstract: Titanium dioxide (TiO2 ) nanomaterials (NMs) are widely used in a diversity of products including cosmetics, pharmaceuticals, food, and inks, despite uncertainties surrounding the potential health risks that they pose to humans and the environment. Previous studies on the genotoxicity of TiO2 have reported discrepant or inconclusive findings in both in vitro and in vivo systems. This study explores the in vivo genotoxic potential of a well-characterized uncoated TiO2 NM with an average diameter of 22 nm (NM-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The results of this MWCNT exposure were obtained by using a powerful technique for the assessment of microvascular function in vivo combined with a well-characterized knockout model. This study also represents one of a handful of attempts to use genetically manipulated animals to investigate molecular mechanisms of nanotoxicity (Aragon et al, 2016; Bagher et al, 2011; Chen et al, 2015; Louro et al, 2014), and is the first in the area of the peripheral microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this MWCNT exposure were obtained by using a powerful technique for the assessment of microvascular function in vivo combined with a well-characterized knockout model. This study also represents one of a handful of attempts to use genetically manipulated animals to investigate molecular mechanisms of nanotoxicity (Aragon et al, 2016; Bagher et al, 2011; Chen et al, 2015; Louro et al, 2014), and is the first in the area of the peripheral microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent in vivo study (Louro et al., ), transgenic C57B1/6 mice harbouring a plasmid containing the bacterial lacZ reporter gene were exposed to TiO 2 nanoparticles (anatase; average diameter 22 nm) with two daily intravenous injections at 10 and 15 mg/kg bw. Top dose was the maximum achievable based on concentration of stable nanoparticle dispersion and the administered volume.…”
Section: Biological and Toxicological Datamentioning
confidence: 99%
“…Other in vivo studies have used other routes of exposure. Negative results in gene and chromosomal mutation tests were obtained in rats injected intravenously (Sadiq et al., ; Louro et al., ). A mild increase in micronuclei in bone marrow, with no concurrent DNA damage detectable by Comet assay, was reported in another recent intravenous study (Dobrzynska et al., ), but the Panel noted some inconsistencies in these results which are regarded of questionable biological significance.…”
Section: Biological and Toxicological Datamentioning
confidence: 99%
“…Therefore, their genotoxicity is an important property for risk assessment. Several in vivo studies related to genotoxic effects of TiO 2 NPs have been reported, but their results are inconsistent [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Almost all of these reports analyzed the micronuclei and DNA damage by the comet assay, which reveals transient genotoxic consequences that occur shortly after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxicity is one of the key factors to assess the carcinogenic risk to humans. Several studies in mice and rats have reported conflicting results of various genotoxic endpoint analyses [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Recently, we reported that TiO 2 NPs have no genotoxic effects in the liver and erythrocytes when intravenously injected into gpt delta mice [17], but there are still reports about their positive effect [18,19].…”
Section: Introductionmentioning
confidence: 99%